(untitled) (Journal of Global Arts Studies, 2023)
Background: The arrival of the post-epidemic era, the domestic economy gradually recovered and developed, people’s living standards of consumption recovered and improved. At the same time, the restaurant industry also continues to develop and recover and expand. For designers, it is undoubtedly a challenge to effectively communicate the entire restaurant brand image. Objective: In the history of art, some artists are in a state of being ignored, which is both normal and abnormal. The normal refers to that an art history is a history with both masking and exposure, while the abnormal means that some important artists are excluded from the vision of art history. Methods: Based on literature research methods, we organized articles and literature materials related to Gao Qipei, explored the origin of Gao Qipei’s "Wonder-advocating" Thought in his painting from the perspectives of his career and personal experience and analyzed the "Wonder-advocating" Thought from multiple angles. Result: There was an expression form of "Wonder-advocating" art in the Ming and Qing Dynasties, and Gao Qipei reflected the pursuit of "curiosity" taste from artists in the Qing Dynasty. Starting from Gao Qipei, the finger and pen have a distinction in painting. In his concept, the finger had many advantages over the pen, which prompted him to use the finger for painting and formed his own unique painting style. Conclusion: It is revealed that Gao Qipei had a "brand new" understanding of painting art under the condition of "Wonder-advocating" Thought, which brought new vitality to Chinese painting art.